BioDiv-Web: Integrating structured project-based learning with citizen science to enhance critical thinking and environmental literacy - Tsaniyah, Uswatul Wadhichatis; Muhdhar, Mimien Henie Irawati Al; Muntholib, Muntholib (STKIP Persada Khatulistiwa Sintang, 2025)
The escalating global biodiversity crisis underscores the critical need for effective educational strategies that promote environmental awareness and competencies. This research and development study addresses this imperative by designing and evaluating